Effect Of Supercharging And Turbocharging In A Multi Cylinder Low Speed Spark Ignition Engine Fuelled By Producer Gas - Mohd Shafie, Mohd Saiful Aizat (2015)
Producer gas has been used successfully in diesel engine with diesel replacement of 60 – 70% but suffers 20 – 30% power de-rating. On the other hand, fully fuelled producer gas in spark ignition (SI) engine suffered significantly high power de-rating about 40 – 70% which makes it undesirable. This research was done to improve producer gas fuelled SI engine in term of brake power, brake thermal efficiency, specific energy consumption, exhaust gas temperature, exhaust gas emissions and economic analysis by means of supercharging and turbocharging both producer gas and air. Research was done on a Perodua Kancil’s 660cc engine. Producer gas was generated from gasification process inside downdraft gasifier with a complete cooling and cleaning system. Speed of producer gas fuelled engine in naturally aspirated (NA) and supercharged (SC) mode was maintained at 1500 rpm, while operation of turbocharged (TC) mode was fixed at 3000 rpm. Load applied to the engine was varied up to 20 Nm which is the maximum load limitation of the utilized dynamometer. SC mode produced similar brake power with gasoline operation at 3.14 kW, while NA and TC mode recorded power de-rating of 70% and 30% respectively. Brake thermal efficiency and specific energy consumption of SC mode was found to be comparable with gasoline operation. Supercharging of both producer gas and air also improved 40% of CO emission compared to naturally aspirated producer gas fuelled engine operation. However the value was still slightly higher than gasoline operation by 30%. High energy input of SC mode contributed mainly by two air compressors make it not financially beneficial. Among all producer gas fuelled engine operation modes, it was believed that TC mode capable of producing optimum engine performance and cost effective, provided that suitable turbocharger system was used to further reduce its power de-rating and improved exhaust gas emission.